The Financial Disclosure Of Companies Listed On The Algerian Stock Exchange During The Period 2010-2020 - Bey, Meryem (Finance and Business Economies Review, 2022)
This study aims to assess the financial disclosure of the companies listed on the Algerian Stock Exchange during the period 2010-2020, as financial disclosure plays a major role in the investors’ decision-making, so the Algiers Stock Exchange obliges the issuing institutions to disclose to protect investors on the one hand, and enhance the efficiency of the stock exchange on the other hand. The study concluded that the institutions listed on the Algerian Stock Exchange adhere to the disclosure system when publicly resorting to savings, and after entering the stock exchange, however, this disclosure does not comply with the Algerian financial accounting system, which requires the issuance of updated systems that are compatible with the Algerian financial accounting system modified and complementary to the current systems.